Weekend woodturning projects : 25 designs to help build your skills - Baker, Mark, 1966- (Guild of Master Craftsman Publications, 2014)
Making use of the six basic tools - spindle roughing gouge, spindle gouge, parting tool, bowl gouge, skew chisel and scrapers, this book introduces a couple of carving tools and a boring tool and explains why and how to use them. Each project will have a list of tools and materials required, drawings with dimensions and a panel on the wood used.